(untitled) (REMUNOM, 2025)
Tutoring in Probability and Statistics plays a strategic role in higher education, functioning not only as an institutional policy for academic support but also as a preventative measure against school dropout. Given the growing demand for tutoring in addition to teaching activities, this practice broadens the scope of the teaching-learning process, extending beyond the classroom and significantly influencing students’ routines, performance, and behavior. This study, with an applied approach and descriptive and exploratory design, sought to analyze the relevance and impacto f tutoring, reaffirming its value as a pedagogical and social resource. To this end, data were collected through electronic forms completed by three groups: students, tutors, and the faculty member in charge. The analysis revealed consonance with the perspectives of Lev Vygotsky and David Kolb, according to which tutoring benefits not only students but also the tutors themselves, stimulating the development of academic, professional, and socio-emotional skills. The findings indicate that the adoption of diverse methodologies, combined with the creation of a welcoming environment and the systematic reinforcement of content, contributes significantly to academic performance and student retention, confirming monitoring as a fundamental support policy for quality and equity in higher education.